THE EFFECT OF HYDRAULIC RETENTION TIME (HRT) AND AERATION RATE ON THE REMOVAL OF COD, TSS, AND COLOR IN BATIK WASTEWATER USING A SEQUENCING BATCH REACTOR (SBR) - Fitiryah, Lailatul; Raden Kokoh Haryo Putro (Lingkar: Journal of Environmental Engineering, 2025)
The batik industry produces liquid waste with high concentrations of organic compounds, synthetic dyes and suspended solids. Based on initial testing, the COD, TSS and Color content exceeds the quality standard limits. The Sequencing Batch Reactor method with a batch operation system is used to process liquid waste and reduce pollutant parameters. There is an adsorption medium with coconut shell activated carbon as a pre-treatment in the efficiency of color parameter removal. The purpose of this study was to analyze the effect of HRT and aeration rate to reduce polluted parameters in batik liquid waste. The HRT variations used were 18, 24, 32, and 38 hours with aeration rates of 7 and 14 L/minute. The results obtained from this study, the most optimal HRT in reducing pollutant TSS parameters is HRT 32 hours with a removal percentage of 71.43%. HRT 38 hours with COD and TSS parameters with a removal percentage of 92.12% and 78.57% and Color parameters 62,39%. The optimal aeration rate is 14 l/minute.